OPTIMALISASI PRODUKSI UMKM RUMAH BOULU MELALUI RE-DESAIN ALAT CETAKAN KUE ULAT SUTERA - Imansyah, Fitri; Batubara, Hafzoh; Djanggu, Noveicalistus H; Sujana, Ivan (Jurnal Abdi Insani, 2024)
Product design is a series of activities that begins with the analysis of perceptions and market opportunities, and ends with the stages of production, sales, and product delivery. Designing can involve creating completely new products or developing existing ones to achieve improved performance. This activity aims to optimize production at UMKM Rumah Boulu through the redesign of silk worm cake molds. Currently, the production process of silk worm cakes uses manual molds that require significant effort and have limited production capacity. This causes difficulties in meeting increased demand, especially during peak seasons. The redesign of the molds uses the Quality Function Deployment (QFD) method and an anthropometric approach to increase production capacity and reduce fatigue and pain in the workers' wrists and shoulders. The redesign results show that the new molds can increase production capacity from 200 grams per mold to 500 grams per mold due to the inclusion of two tubes. Additionally, the molds are designed to be more ergonomic, allowing workers to use them comfortably in a seated position, thus reducing excessive fatigue. A business feasibility analysis using the methods of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Profitability Index, and Return on Investment (ROI) indicates that this business is very feasible. Thus, the redesign of the silk worm cake molds not only improves production efficiency but also enhances the well-being of workers at UMKM Rumah Boulu.